Minat Menggunakan E-Wallet pada Generasi Milenial dengan Pendekatan UTAUT (Unified Theory of Acceptance Use of Technology) - Damayanti, Sindi Livia; Yani, Yepi; Asnaini, Asnaini; Afrianty, Nonie (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2021)
This study aims to examine the influences of the factors contained in the UTAUT theory to the interest in using e-wallets for the millennials. This study used the analysis of Structural Equation Modeling (SEM) with SmartPLS software. The sample used is 100 millennials respondent in Kota Bengkulu. The sampling technique used was purposive sampling. The purposive sampling is used because this study requires certain criteria such as the age of the respondents in the birth range 1981-2000, using an e-wallet and live in Kota Bengkulu. The data collection technique used google form questionnaire and shared to millennials through social media such as WhatsApp, Instagram, and Facebook. The results of this study indicate that three of the factors in the UTAUT tested consisting of business expectations, social influences, and facility conditions have a positive and significant influences to the interest of the millennials to use e-wallets in Kota Bengkulu, while the performance expectation factor does not have a positive and Significant influences to millennials interest in using e-wallets in the Bengkulu City